Increased Risk of Atrial and Ventricular Arrhythmia in Long-Lasting Psoriasis Patients. (3rd April 2013) - Simsek, Hakki; Sahin, Musa; Akyol, Aytac; Akdag, Serkan; Ozkol, Hatice Uce; Gumrukcuoglu, Hasan Ali; Gunes, Yilmaz
Abstract : Background . Several reports have demonstrated an association between psoriasis and cardiovascular diseases. P wave dispersion (PWD) is the most important electrocardiographic (ECG) markers used to evaluate the risk of atrial arrhythmias. QT dispersion (QTD) can be used to assess homogeneity of cardiac repolarization and may be a risk for ventricular arrhythmias. Aim . To search PWD and QTD in patients with psoriasis. Methods . Ninety-four outpatient psoriasis patients and 51 healthy people were evaluated by physical examination, 12-lead ECG, and transthoracic echocardiography. Severity of the psoriasis was evaluated by psoriasis area and severity index (PASI). Results . Mean disease duration was 129.4 ± 83.9 (range, 3–360) months and PASI ranged from 0 to 34.0 (mean ± SD; 7.6 ± 6.7 ). Compared to control group, psoriatic patients had significantly shorter Pmax and Pmin durations, longer QTcmax, and greater PWD and QTcD. Transmitral deceleration time (DT) and isovolumetric relaxation time (IVRT) were significantly longer among psoriasis patients. QTcD and PWD were significantly correlated with disease duration (r = 0.693, P < 0.001, and r = 0.368, P = 0.003, resp.). Conclusions . In this study, we found that both PWD and QTcD are increased in psoriasis patients compared to healthy subjects. In addition, they had longer DT and IVRT.